Friction member, friction material composition, friction material and vehicle
Patent Information
- Application Number
- JP2020147510
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0010】 本発明によれば、銅の含有量が0.5質量%未満、かつ、スチール繊維の含有量が25質量%以下であっても、フェード時の摩擦係数と高温高速制動時の耐摩耗性が良好な摩擦材を有する摩擦部材、前記摩擦材を提供し得る摩擦材組成物、前記摩擦材、及び前記摩擦部材又は前記摩擦材を搭載した車両を提供することができる。
Smart Images

Figure 0007642995000002 
Figure 0007642995000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a friction member, a friction material composition, a friction material, and a vehicle. [Background technology]
[0002] Friction materials such as disc brake pads and brake linings are used in automobiles for braking. Friction materials perform their braking function by rubbing against opposing materials such as disc rotors and brake drums. For this reason, friction materials are required to have a good friction coefficient, wear resistance (long life of friction materials), etc.
[0003] Friction materials are broadly divided into semi-metallic materials that contain 30-60% by mass of steel fibers as a fiber base material, low-steel materials that contain less than 30% by mass of steel fibers, and NAO (Non Asbestos Organic) materials that do not contain steel fibers. Friction materials with a low content of steel fibers, such as low-steel materials and NAO materials, are less aggressive to the mating material, the disc rotor, and therefore have the characteristic of being able to suppress the wear of the disc rotor and the generation of brake squeal. On the other hand, low-steel materials and NAO materials have a low content of steel fibers, making it difficult to ensure sufficient braking performance. To compensate for this, copper powder and copper fibers, which are highly effective in suppressing the decrease in the friction coefficient during high-speed braking at high temperatures, have been used.
[0004] However, in recent years, it has been suggested that friction materials containing copper, copper alloys, etc. may pollute rivers, lakes, etc., because the friction materials contain copper in the wear powder generated during braking. Copper is blended into friction materials in the form of fibers, powder, etc., and is an effective component for imparting thermal conductivity. In compositions that do not contain copper, the thermal conductivity is reduced, so that the heat at the friction interface does not diffuse during braking at high temperatures, increasing the amount of wear of the friction material, and the amount of decomposition gas during braking increases, resulting in poor fade resistance.
[0005] As a friction material with improved fade resistance, a friction material that contains a large amount of rock wool as a base material to ensure porosity (see, for example, Patent Document 1) has been proposed. In addition, a friction material that uses a titanate having a scale-like, columnar or plate-like tunnel crystal structure in combination with a titanate having a layered crystal structure has been proposed as a friction material that does not contain copper and has improved wear resistance and stability of friction coefficient during braking at high temperatures and high loads (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-158904 A [Patent Document 2] JP 2019-48989 A Summary of the Invention [Problem to be solved by the invention]
[0007] The technology described in Patent Document 1 improves fade resistance, while the technology described in Patent Document 2 aims to improve wear resistance and stability of friction coefficient during high-speed braking at high temperatures in a composition that does not contain copper. However, even with these friction materials, it cannot be said that they are yet sufficient in terms of both fade resistance and wear resistance during high-speed braking at high temperatures.
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a friction member having a friction material that has a good friction coefficient during fade and abrasion resistance during high-temperature, high-speed braking even when the copper content is less than 0.5% by mass and the steel fiber content is 25% by mass or less, a friction material composition capable of providing the friction material, the friction material, and a vehicle equipped with the friction member or the friction material. [Means for solving the problem]
[0009] As a result of intensive research conducted by the present inventors to achieve the above object, it has been found that the above problems can be solved by the present invention described below. That is, the present invention relates to the following [1] to
[15] . [1] A friction member having a friction material and a backing metal, The friction material has a copper content of less than 0.5% by mass based on a total amount of the friction material, a steel fiber content of 25% by mass or less based on a total amount of the friction material, and a calcium sulfate fiber content of 1 to 20% by mass based on a total amount of the friction material. [2] The friction member according to the above [1], wherein the calcium sulfate fibers have an average fiber length of 1 to 200 μm. [3] The friction member according to the above [1] or [2], wherein the calcium sulfate fibers have an average fiber diameter of 0.1 to 20 μm. [4] The friction member according to any one of the above [1] to [3], wherein the calcium sulfate fibers have an average aspect ratio (fiber length / fiber diameter) of 5 to 200. [5] The friction member according to any one of the above [1] to [4], wherein the calcium sulfate fibers are fibers made of type II anhydrous gypsum. [6] The friction member according to any one of the above [1] to [5], further comprising titanate in an amount of 2 to 40 mass % based on the total amount of the friction material. [7] A vehicle equipped with the friction member according to any one of the above items [1] to [6]. [8] A friction material composition having a copper content of less than 0.5% by mass and a steel fiber content of 25% by mass or less, the friction material composition containing 1 to 20% by mass of calcium sulfate fiber. [9] The friction material composition according to the above [8], wherein the calcium sulfate fibers have an average fiber length of 1 to 200 μm.
[10] The friction material composition according to the above [8] or [9], wherein the calcium sulfate fibers have an average fiber diameter of 0.1 to 20 μm.
[11] The friction material composition according to any one of the above [8] to
[10] , wherein the calcium sulfate fibers have an average aspect ratio (fiber length / fiber diameter) of 5 to 200.
[12] The friction material composition according to any one of the above [8] to
[11] , wherein the calcium sulfate fibers are fibers made of type II anhydrous gypsum.
[13] The friction material composition according to any one of the above [8] to
[12] , further comprising 2 to 40 mass % of a titanate.
[14] A friction material comprising the friction material composition according to any one of the above items [8] to
[13] .
[15] A vehicle equipped with the friction material described in
[14] above. Effect of the Invention
[0010] According to the present invention, even if the copper content is less than 0.5 mass % and the steel fiber content is 25 mass % or less, it is possible to provide a friction member having a friction material that has a good friction coefficient during fade and abrasion resistance during high-temperature, high-speed braking, a friction material composition capable of providing the friction material, the friction material, and a vehicle equipped with the friction member or the friction material. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram of a cross section of a friction member (disc brake pad) in which a friction material (upper layer) is disposed on one surface of a back plate via a lower layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the friction member, friction material composition, friction material, and vehicle according to the embodiments of the present invention will be described in detail. However, in the following embodiments, the components are not essential unless specifically stated otherwise. The same applies to the numerical values and their ranges, and they do not limit the present invention.
[0013] In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in the Examples. Furthermore, in this specification, when there are multiple substances corresponding to each component, the content of each component in the friction material and friction material composition means the total content of the multiple substances present in the friction material and friction material composition, unless otherwise specified. The present invention also includes any combination of the features described in this specification.
[0014] [Friction members, friction materials, and friction material compositions] The friction member according to the present embodiment is a friction member having a friction material and a backing metal, and the friction material contains less than 0.5% by mass of copper and 25% by mass or less of steel fibers and calcium sulfate fibers, respectively, based on the total amount of the friction material.
[0015] The friction material composition according to the present embodiment is a friction material composition having a copper content of less than 0.5 mass % and a steel fiber content of 25 mass % or less, and containing 1 to 20 mass % of calcium sulfate fibers. The friction material according to the present embodiment is a friction material containing the friction material composition according to the present embodiment.
[0016] The friction material of the friction member of this embodiment and the friction material containing the friction material composition of this embodiment (both are referred to as "friction material of this embodiment" in the following description) will be described in detail below. The types of components contained in the friction material composition of this embodiment and the manufacturing method thereof are explained in the same manner as for the friction material of this embodiment below, and the preferred embodiments are also all the same. The preferred ranges of the contents of the components in the friction material composition are the same as those explained for the friction material of this embodiment, but the content standard is "the total amount of the friction material composition".
[0017] <Copper> The friction material of the present embodiment has a copper content of less than 0.5 mass % with respect to the total amount of the friction material. In this specification, the phrase "the copper content is less than 0.5% by mass with respect to the total amount of the friction material" also includes the case where the copper content is 0% by mass. The above-mentioned "copper" refers to, for example, copper in a fibrous or powder form; copper alloys, copper compounds, and the like. When the friction material of the present embodiment contains copper, the copper content is preferably 0.3 mass % or less, more preferably 0.1 mass % or less, and further preferably 0.05 mass % or less, based on the total amount of the friction material. The friction material of the present embodiment may not contain copper. However, in this specification, "not containing" copper is a definition that excludes intentional blending of copper, and is not a definition that excludes unintentional inclusion of copper.
[0018] <Steel fiber> The friction material of the present embodiment is an invention that has been developed based on a composition that reduces the amount of steel fibers contained, thereby suppressing aggressiveness to the disc rotor and the occurrence of brake squeal, and that has a composition that provides sufficient braking performance without using copper. Therefore, the friction material of the present embodiment has a steel fiber content of 25 mass % or less with respect to the total amount of the friction material. In this specification, the phrase "steel fiber content is 25 mass % or less" also includes the case where the steel fiber content is 0 mass %. When the friction material of the present embodiment contains steel fibers, the content is not particularly limited, but from the viewpoint of improving the wear resistance of the disc rotor and suppressing the occurrence of brake squeal, the content is preferably 20 mass % or less, more preferably 10 mass % or less, and even more preferably 1 mass % or less, based on the total amount of the friction material. The friction material of the present embodiment may not contain steel fibers.
[0019] <Calcium sulfate fiber> The friction material of the present embodiment contains calcium sulfate fibers, and thus achieves both a good friction coefficient during fading and good wear resistance during high-speed braking at high temperatures. The reason for this is unclear, but is presumed to be as follows. Calcium sulfate fiber is a compound having a fibrous shape that exhibits a reinforcing effect in friction materials, and is stronger than organic fibers, so that it can increase the mechanical strength of friction materials. Furthermore, calcium sulfate fiber is less likely to decompose or burn than organic fibers even when exposed to high temperatures, so it is believed that the reinforcing effect on the friction material is not lost even in harsh environments such as high-temperature, high-speed braking, and that this can suppress the wear of the brake pads. On the other hand, calcium sulfate fiber is not a material with a high Mohs hardness, so it is believed that this can improve the balance between the friction coefficient during fading and the wear resistance during high-temperature, high-speed braking without adversely affecting other physical properties, including the friction coefficient. In this specification, the term "calcium sulfate fiber" refers to calcium sulfate having a ratio of the maximum length to the minimum length (aspect ratio) of 5 or more.
[0020] Calcium sulfate is roughly classified into dihydrate gypsum (calcium sulfate dihydrate), hemihydrate gypsum (calcium sulfate hemihydrate) and anhydrous gypsum (calcium sulfate anhydrous) according to the form of the water of crystallization, and calcium sulfate anhydrous is further classified into type I, type II and type III according to the difference in the crystal system. Among these, the calcium sulfate fiber contained in the friction material of the present embodiment is preferably a fiber made of anhydrous gypsum (calcium sulfate anhydrous), and more preferably a fiber made of type II anhydrous gypsum from the viewpoint of suppressing the change in the friction coefficient due to water absorption and the expansion and contraction of the friction material due to the volume change. The calcium sulfate fibers may be made of one type of calcium sulfate alone or two or more types of calcium sulfate may be used in combination.
[0021] (fiber length) The average fiber length of the calcium sulfate fibers is not particularly limited, but from the viewpoints of dispersibility of the calcium sulfate fibers and wear resistance of the brake pad, it is preferably 1 to 200 μm, more preferably 3 to 100 μm, further preferably 5 to 50 μm, and particularly preferably 10 to 20 μm. The minimum fiber length of the calcium sulfate fibers is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and particularly preferably 1 μm or more. The maximum fiber length of the calcium sulfate fibers is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 200 μm or less, and particularly preferably 100 μm or less. The average fiber length of calcium sulfate fibers can be calculated as the average value by, for example, measuring the fiber lengths of 50 arbitrary calcium sulfate fibers observed with a scanning electron microscope (SEM) etc. The maximum fiber length and the minimum fiber length of calcium sulfate fibers mean the maximum fiber length and the minimum fiber length of the arbitrary 50 calcium sulfate fibers observed in the measurement of the average fiber length.
[0022] (fiber diameter) The average fiber diameter of the calcium sulfate fibers is not particularly limited, but from the viewpoints of dispersibility of the calcium sulfate fibers and wear resistance of the brake pad, it is preferably 0.1 to 20 μm, more preferably 0.2 to 10 μm, even more preferably 0.3 to 5 μm, and particularly preferably 0.5 to 2 μm. The minimum fiber diameter of the calcium sulfate fibers is preferably 0.02 μm or more, more preferably 0.04 μm or more, even more preferably 0.07 μm or more, and particularly preferably 0.1 μm or more. The maximum fiber diameter of the calcium sulfate fibers is preferably 100 μm or less, more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 10 μm or less. The average fiber diameter of calcium sulfate fibers can be calculated as the average value of the fiber diameters of 50 random calcium sulfate fibers observed with a scanning electron microscope (SEM) or the like. The maximum and minimum fiber diameters of calcium sulfate fibers refer to the maximum and minimum fiber diameters of the 50 random calcium sulfate fibers observed in the measurement of the average fiber diameter.
[0023] (Aspect Ratio) The average aspect ratio (fiber length / fiber diameter) of the calcium sulfate fibers is not particularly limited, but from the viewpoints of dispersibility of the calcium sulfate fibers and the wear resistance of the brake pad, it is preferably 5 to 200, more preferably 6 to 100, even more preferably 8 to 50, and particularly preferably 10 to 20. The average aspect ratio (fiber length / fiber diameter) of calcium sulfate fibers can be calculated, for example, by measuring the aspect ratios of any 50 calcium sulfate fibers using a scanning electron microscope (SEM) or the like, and averaging the aspect ratios.
[0024] The content of calcium sulfate fibers in the friction material of the present embodiment is not particularly limited, but from the viewpoint of achieving both a good friction coefficient during fading and good wear resistance during high-temperature, high-speed braking, the content is preferably 1 to 20 mass %, more preferably 2 to 15 mass %, and even more preferably 3 to 10 mass %, based on the total amount of the friction material.
[0025] <Inorganic fillers, organic fillers, fiber base materials, binding materials> The friction material of the present embodiment preferably contains an inorganic filler, an organic filler, a fibrous base material containing the calcium sulfate fibers, and a binder. In this specification, a fiber base material other than calcium sulfate fibers may be referred to as "other fiber base materials." When simply referred to as "fiber base material," this refers to the entire fiber base material including calcium sulfate fibers and other fiber base materials. Each component will be described in more detail below.
[0026] <Inorganic filler> The inorganic filler may be appropriately selected according to the purpose from those capable of exerting the function as a friction modifier that adjusts the heat resistance, wear resistance, friction coefficient, etc. of the friction material. In the present embodiment, the definition of "inorganic filler" does not include fibrous ones (i.e., inorganic fibers). The inorganic fillers may be used alone or in combination of two or more kinds.
[0027] Examples of inorganic fillers include titanates such as potassium titanate (potassium 6-titanate, potassium 8-titanate), lithium potassium titanate, potassium magnesium titanate, and sodium titanate; metal sulfides such as tin sulfide, iron sulfide, bismuth sulfide, molybdenum sulfide, zinc sulfide, antimony sulfide, tungsten sulfide, and manganese sulfide; graphite such as natural graphite and artificial graphite; metal oxides or non-metal oxides such as iron oxide (III), triiron tetroxide, aluminum oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, zinc oxide, bismuth oxide, and silicon dioxide; metal powders such as iron powder, tin powder, zinc powder, aluminum powder, and alloy powders thereof; metal sulfates such as barium sulfate and calcium sulfate; metal hydroxides such as calcium hydroxide; metal silicates such as zirconium silicate and calcium silicate; metal carbonates such as sodium carbonate, calcium carbonate, and magnesium carbonate; coke; and minerals such as mica, dolomite, vermiculite, talc, clay, mullite, chromite, and zeolite. Among these, it is preferable to contain at least one selected from the group consisting of titanates, metal sulfides, graphite, metal oxides, non-metal oxides, metal silicates, metal powders, barium sulfate, and calcium hydroxide.
[0028] Average particle size of inorganic filler (D 50 ) may be appropriately selected depending on the material, but is usually selected in the range of 0.1 to 100 μm, and may be 0.5 to 50 μm, or 1 to 30 μm. In this specification, the average particle diameter (D 50 ) is the D measured using the laser diffraction particle size distribution measurement method. 50 The mean particle size (D 50 ) can be measured, for example, using a laser diffraction / scattering type particle size distribution analyzer, product name: LA-920 (manufactured by Horiba, Ltd.). The inorganic filler that is preferably contained in the friction material of the present embodiment will be described in more detail below.
[0029] (Titanic acid) Among the titanates listed above, potassium 6-titanate and potassium 8-titanate are preferred from the viewpoint of the friction coefficient. The titanate is preferably non-acicular. Non-acicular titanates include plate-like titanates having shapes such as polygons, circles, and ellipses, and titanates having irregular shapes. When the friction material of the present embodiment contains a titanate, the content thereof is not particularly limited, but is preferably 2 to 40 mass %, more preferably 10 to 35 mass %, and even more preferably 15 to 30 mass %, based on the total amount of the friction material.
[0030] (metal sulfide) As the metal sulfide, among those listed above, from the viewpoint of the stability of the friction coefficient during normal braking, antimony sulfide, tin sulfide, iron sulfide, bismuth sulfide, molybdenum sulfide, and zinc sulfide are preferred, and antimony sulfide is more preferred. When the friction material of the present embodiment contains a metal sulfide, the content thereof is not particularly limited, but from the viewpoints of wear resistance and friction coefficient, the content is preferably 0.5 to 10 mass %, more preferably 1 to 7 mass %, and even more preferably 2 to 5 mass %, based on the total amount of the friction material.
[0031] (graphite) When the friction material of the present embodiment contains graphite, the content thereof is not particularly limited, but from the viewpoints of wear resistance and friction coefficient, the content is preferably 1 to 15 mass %, more preferably 2 to 10 mass %, and even more preferably 3 to 8 mass %, based on the total amount of the friction material.
[0032] (Metal oxides, non-metal oxides, metal silicates) Of the metal oxides, non-metal oxides and metal silicates listed above, zirconium oxide, magnesium oxide, zirconium silicate and aluminum oxide are preferred, with zirconium oxide being more preferred. When the friction material of the present embodiment contains one or more selected from the group consisting of metal oxides, non-metal oxides, and metal silicates, the content thereof is not particularly limited, but from the viewpoints of wear resistance and friction coefficient, the content thereof is preferably 17 to 40 mass %, more preferably 20 to 35 mass %, and even more preferably 25 to 32 mass %, based on the total amount of the friction material.
[0033] (metal powder) Of the metal powders listed above, zinc powder is preferred. When the friction material of the present embodiment contains metal powder, the content thereof is not particularly limited, but from the viewpoints of rust prevention, wear resistance, and friction coefficient, the content is preferably 0.1 to 10 mass %, more preferably 0.5 to 5 mass %, and even more preferably 1 to 4 mass %, based on the total amount of the friction material.
[0034] (Barium Sulfate) The barium sulfate acts merely as a filler to adjust the volume of the friction material, i.e., the amount of barium sulfate depends on the amount of other ingredients, and the barium sulfate can be used to make up the remainder to make up the desired amount of friction material.
[0035] (Calcium hydroxide) When the friction material of the present embodiment contains calcium hydroxide, the content thereof is not particularly limited, but from the viewpoint of appropriately adjusting the pH, the content is preferably 0.5 to 10 mass %, more preferably 1 to 8 mass %, and even more preferably 2 to 5 mass %, based on the total amount of the friction material.
[0036] The total content of the inorganic filler in the friction material of the present embodiment is not particularly limited, but from the viewpoints of wear resistance and friction coefficient, it is preferably 40 to 90 mass %, more preferably 50 to 85 mass %, and even more preferably 60 to 75 mass %, based on the total amount of the friction material.
[0037] <Organic filler> The organic filler is contained as a friction modifier for improving the noise and vibration performance, wear resistance, etc. of the friction material. Here, in the present embodiment, the definition of the organic filler does not include fibrous ones (i.e., organic fibers described later).
[0038] Examples of the organic filler include cashew dust and rubber components, and it is preferable to use cashew dust and rubber components in combination. The organic filler may be used alone or in combination of two or more kinds.
[0039] (Cashew dust) The cashew dust may be, for example, a powder obtained by polymerizing and hardening cashew nut shell oil. The cashew dust is preferably unmodified cashew dust. Cashew dust is generally classified into, for example, brown, brown-black, black, etc., depending on the type of hardener used in the hardening reaction. Average particle size of cashew dust (D 50 ) is not particularly limited, but from the viewpoint of dispersibility and the like, it is preferably from 10 to 700 μm, more preferably from 20 to 500 μm, and even more preferably from 30 to 350 μm. When the friction material of the present embodiment contains cashew dust, the content thereof is not particularly limited, but from the viewpoint of sound vibration performance, the content is preferably 1 to 15 mass %, more preferably 2 to 10 mass %, and even more preferably 4 to 8 mass %, based on the total amount of the friction material.
[0040] (Rubber component) The rubber component may be any known material used in friction materials, such as natural rubber, synthetic rubber, etc. Examples of synthetic rubber include acrylonitrile-butadiene rubber (NBR), acrylic rubber, isoprene rubber, polybutadiene rubber (BR), styrene butadiene rubber (SBR), silicone rubber, crushed powder of tire tread rubber (sometimes referred to as rubber powder), butyl rubber, etc. When the friction material of the present embodiment contains a rubber component, the content thereof is not particularly limited, but from the viewpoints of the elastic modulus, vibration damping property, heat resistance, strength, etc. of the friction material, the content thereof is preferably 0.1 to 15 mass %, more preferably 0.2 to 10 mass %, and even more preferably 0.3 to 5 mass %, based on the total amount of the friction material.
[0041] The total content of the organic filler in the friction material of the present embodiment is not particularly limited, but from the viewpoints of sound vibration performance, heat resistance, and friction material strength, it is preferably 2 to 20 mass %, more preferably 4 to 15 mass %, and even more preferably 6 to 12 mass %, based on the total amount of the friction material.
[0042] <Other fiber base materials> Examples of the other fiber substrates include organic fibers, inorganic fibers other than calcium sulfate fibers, etc. The other fiber substrates may be used alone or in combination of two or more kinds.
[0043] -Organic fiber- The friction material of the present embodiment preferably contains organic fibers, which are fibrous materials whose main component is an organic substance. Examples of organic fibers include hemp, cotton, aramid fibers, cellulose fibers, acrylic fibers, and phenolic resin fibers (having a cross-linked structure). As the organic fiber, aramid fiber is preferable from the viewpoint of heat resistance.
[0044] When the friction material of the present embodiment contains organic fibers, the content thereof is not particularly limited, but from the viewpoints of the shear strength, crack resistance, wear resistance, etc. of the friction material, the content thereof is preferably 0.1 to 10 mass %, more preferably 0.5 to 6 mass %, and even more preferably 1 to 4 mass %, based on the total amount of the friction material.
[0045] - Inorganic fibers other than calcium sulfate fibers - Examples of inorganic fibers other than calcium sulfate fibers include mineral fibers, glass fibers, metal fibers, ceramic fibers, biodegradable ceramic fibers, sepiolite (α-type sepiolite and β-type sepiolite), attapulgite, potassium titanate fibers, silica alumina fibers, flame-resistant fibers, etc. Among these, mineral fibers are preferred.
[0046] Mineral fibers are man-made inorganic fibers that are melt-spun using blast furnace slag such as slag wool, basalt such as basalt fiber, and other natural rocks as the main components. Examples of mineral fibers include SiO2, Al2O3, CaO, MgO, FeO, Na2O, and mineral fibers containing one or more of these compounds. Mineral fibers containing aluminum are preferred, mineral fibers containing Al2O3 are more preferred, and mineral fibers containing Al2O3 and SiO2 are even more preferred. The mineral fibers may or may not be surface-treated, and surface-treated and non-surface-treated mineral fibers may be used in combination. The average fiber length of the mineral fibers is preferably 500 μm or less, more preferably 100 to 400 μm, and even more preferably 120 to 340 μm.
[0047] When the friction material of the present embodiment contains inorganic fibers other than calcium sulfate fibers, the content thereof is not particularly limited, but is preferably 0.1 to 15 mass %, more preferably 1 to 10 mass %, and even more preferably 3 to 7 mass %, based on the total amount of the friction material.
[0048] The total content of the fiber base material in the friction material of the present embodiment is not particularly limited, but from the viewpoints of wear resistance and friction coefficient, it is preferably 2 to 30 mass %, more preferably 4 to 25 mass %, and even more preferably 6 to 20 mass %, based on the total amount of the friction material.
[0049] <Binding material> The binder binds together the organic filler, fibrous base material, etc. contained in the friction material, thereby providing strength to the friction material. The binder may be used alone or in combination of two or more kinds. As the binder, a thermosetting resin that is usually used for friction materials can be used. Examples of the thermosetting resin include various modified phenolic resins such as phenolic resin, acrylic rubber modified phenolic resin, silicone modified phenolic resin, cashew modified phenolic resin, epoxy modified phenolic resin, and alkylbenzene modified phenolic resin. Among these, phenolic resin is preferred. As the phenolic resin, for example, straight novolac phenolic resin is preferred.
[0050] The content of the binder in the friction material of the present embodiment is not particularly limited, but from the viewpoints of the strength of the friction material and the sound vibration performance, it is preferably 2 to 20 mass %, more preferably 4 to 15 mass %, and even more preferably 6 to 12 mass %, based on the total amount of the friction material.
[0051] <Other ingredients> The friction material of the present embodiment may or may not contain materials other than the above-mentioned components, as necessary. When the friction material of the present embodiment contains the other materials, the content thereof may be, for example, 0.01 to 10 mass % or 0.1 to 5 mass % relative to the total amount of the friction material.
[0052] <Methods of producing friction member, friction material, and friction material composition> The friction member, friction material, and friction material composition of the present embodiment can be produced by a known method. Specifically, the above components can be uniformly mixed using a mixer such as a Lödige (registered trademark) mixer, a pressure kneader, or an Eirich (registered trademark) mixer to obtain a friction material composition. The obtained friction material composition is preformed in a molding die as necessary, and then molded under conditions of a molding temperature of 130 to 160°C, a molding pressure of 20 to 50 MPa, and a molding time of 3 to 10 minutes, and the obtained molded product is heat-treated at 180 to 230°C for 3 to 5 hours to obtain a friction material and a friction member. Note that painting, scorching, polishing, etc. may be performed as necessary.
[0053] The friction material of the present embodiment is used, for example, in the following aspects (1) to (3). (1) Composition of friction material only. (2) A friction member having a backing metal and the friction material of the present embodiment formed on the backing metal to form a friction surface. (3) In the configuration of (2) above, a primer layer for surface modification to enhance the adhesive effect of the backing metal and an adhesive layer for bonding the backing metal and the friction member are further interposed between the backing metal and the friction member. Among these, it is preferable to use the above-mentioned (2) or (3) as a friction member. The backing metal is used to improve the mechanical strength of the friction member, and examples of the material thereof include metals such as iron and stainless steel; and fiber-reinforced plastics such as inorganic fiber-reinforced plastics and carbon fiber-reinforced plastics. The primer layer and adhesive layer may be any layer that is generally used for friction members such as brake shoes.
[0054] An embodiment of the friction member of this embodiment will be specifically described with reference to FIG. 1. The friction member of this embodiment is composed of a back plate 1, the friction material of this embodiment (also referred to as an upper layer in the case of FIG. 1) 2, and an underlayer 3, and the friction material (upper layer) 2 is fixed to a surface 11 (here, the upper surface of the back plate 1) on which the friction material of the back plate 1 is arranged, via the underlayer 3. The friction material of this embodiment can be used as the above-mentioned "upper layer" or the above-mentioned "underlayer", but is preferably used as the "upper layer". The "upper layer" is the friction material that becomes the friction surface of the friction member, and the "underlayer" is a layer that is interposed between the friction material that becomes the friction surface of the friction member and the back metal, and is arranged for the purpose of improving the shear strength and crack resistance near the adhesive part between the friction material and the back metal.
[0055] The friction material and friction member of the present embodiment are suitable as friction materials and friction members such as disc brake pads and brake linings for automobiles and the like. Furthermore, the friction material of the present embodiment can also be used as a friction material for clutch facings, electromagnetic brakes, holding brakes, etc. by subjecting it to processes such as molding, processing, and attachment into a desired shape.
[0056] [vehicle] The present invention also provides a vehicle equipped with the friction material or friction member of the present embodiment. For example, the friction member of the present embodiment may be used in a disc brake pad, a brake lining, a clutch facing, an electromagnetic brake, a holding brake, etc. Examples of the vehicle include various automobiles including four-wheeled automobiles and motorcycles, such as large automobiles, medium-sized automobiles, standard automobiles, large special-purpose automobiles, small special-purpose automobiles, large motorcycles, and standard motorcycles. EXAMPLES
[0057] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following examples.
[0058] [Making disc brake pads] <Examples 1 to 4 and Comparative Examples 1 to 4> The materials were blended according to the blending ratios (mass %) shown in Table 1 to obtain each friction material composition. Next, this friction material composition was mixed in a Lödige mixer (manufactured by Matsubo Co., Ltd., product name: Lödige (registered trademark) mixer M20), and the resulting mixture was heated and pressure molded together with an iron backing (thickness 6 mm) using a molding press (manufactured by Technomarusichi Co., Ltd.) The resulting molded product was heat treated at 200°C for 3.5 hours, polished using a rotary polisher, and scorched at 500°C for 3 minutes. Thickness 10mm, projected area 50cm 2 Thus, a disc brake pad having the above friction material was obtained.
[0059] Details of the calcium sulfate fibers used in the examples are as follows. (fiber length) Average fiber length: 16.2μm Maximum fiber length: 85.4μm Minimum fiber length: 2.9μm (fiber diameter) Average fiber diameter: 1.1μm Maximum fiber diameter: 5.4μm Minimum fiber diameter: 0.15μm (Aspect Ratio) Average aspect ratio: 16.2 (Crystal structure) Crystal structure: Type II anhydrite (insoluble anhydrite) The average fiber length, average fiber diameter and average aspect ratio of the calcium sulfate fibers were calculated by observing 50 random calcium sulfate fibers with a scanning electron microscope (manufactured by JEOL Ltd., model number: JSM-6010PLUS / LA), measuring the fiber length, fiber diameter and aspect ratio for each of the fibers, and calculating the average values thereof. The maximum fiber length, minimum fiber length, maximum fiber diameter, and minimum fiber diameter of the calcium sulfate fibers were determined as the maximum fiber length, minimum fiber length, maximum fiber diameter, and minimum fiber diameter of any 50 calcium sulfate fibers observed in the measurement of the average fiber length and average fiber diameter. As for the components other than those mentioned above that were used in common in each of the Examples and Comparative Examples, the same materials were used in all of the Examples and Comparative Examples.
[0060] [General performance test] The general performance test was conducted in accordance with JASO C406 (general performance test). Specifically, a 1 / 5 scale tester (inertia 3.0 kg m 2 ) and a 19 mm × 44 mm test piece cut out from the above disc brake pad were used to determine the minimum average friction coefficient μ in the first fade test and the minimum average friction coefficient μ in the second fade test. The results are shown in Table 1.
[0061] [High temperature and high speed braking test] After carrying out the general performance tests, the rotor temperature was cooled to below 50°C, and after the temperature-raising braking, braking was carried out 15 times at 40-second intervals from 150km / h to 50km / h with a deceleration rate of 0.4G, and the amount of brake pad wear after the test was calculated. The results are shown in Table 1.
[0062] [Table 1]
[0063] As can be seen from Table 1, the friction material of Comparative Example 1 containing no calcium sulfate fibers had a relatively good minimum value of the average friction coefficient μ in the fade test, but the brake pad wear amount during high-speed braking at high temperature was insufficient. The friction material of Comparative Example 2, in which part of the barium sulfate was replaced with aramid fiber in comparison with the friction material of Comparative Example 1 as a reference, showed good brake pad wear during high-speed braking at high temperature, but the minimum value of the average friction coefficient μ in the fade test was insufficient. In addition, the friction material of Comparative Example 3, in which part of the barium sulfate was replaced with mineral fiber, was compared with the friction material of Comparative Example 1 as a reference, and the minimum value of the average friction coefficient μ in the fade test was relatively good, but the brake pad wear amount during high-speed braking at high temperatures was poor. In addition, the friction material of Comparative Example 4, in which potassium titanate was partially replaced with barium sulfate, exhibited significantly worse brake pad wear during high-speed braking at high temperatures, compared to the friction material of Comparative Example 1. In contrast, with the friction material of Comparative Example 1 as the reference, Examples 1 and 2 in which part of the barium sulfate was replaced with calcium sulfate fiber, Example 3 in which the mineral fiber was replaced with calcium sulfate fiber, and Example 4 in which part of the potassium titanate was replaced with calcium sulfate fiber all showed good minimum average friction coefficient μ in the fade test and brake pad wear amount in the high-temperature, high-speed braking test, and it was found that these were compatible. [Explanation of symbols]
[0064] 1 Backplate 11 Surface of the back plate on which the friction material is placed 12 The other side of the back plate 2 Friction material (top material) 3 Underlayment
Claims
1. A friction member having a friction material and a backing metal, The friction material contains less than 0.5% by mass of copper and 25% by mass or less of steel fibers based on the total amount of the friction material, and contains 1 to 20% by mass of calcium sulfate fibers based on the total amount of the friction material, A friction member comprising a titanate (excluding potassium titanate whiskers) in an amount of 2 to 40 mass % based on the total amount of the friction material.
2. 2. The friction member according to claim 1, wherein the calcium sulfate fibers have an average fiber length of 1 to 200 μm.
3. 3. The friction member according to claim 1, wherein the calcium sulfate fibers have an average fiber diameter of 0.1 to 20 μm.
4. The friction member according to any one of claims 1 to 3, wherein the calcium sulfate fibers have an average aspect ratio (fiber length / fiber diameter) of 5 to 200.
5. The friction member according to any one of claims 1 to 4, wherein the calcium sulfate fibers are fibers made of type II anhydrous gypsum.
6. The friction member according to claim 1, wherein the content of the steel fibers is 1 mass % or less relative to the total amount of the friction material.
7. A vehicle equipped with the friction member according to any one of claims 1 to 6.
8. The copper content is less than 0.5% by mass, the steel fiber content is 25% by mass or less, and calcium sulfate fiber is contained in an amount of 1 to 20% by mass. A friction material composition containing 2 to 40 mass % of a titanate (excluding potassium titanate whiskers).
9. 9. The friction material composition according to claim 8, wherein the calcium sulfate fibers have an average fiber length of 1 to 200 μm.
10. The friction material composition according to claim 8 or 9, wherein the calcium sulfate fibers have an average fiber diameter of 0.1 to 20 μm.
11. The friction material composition according to any one of claims 8 to 10, wherein the calcium sulfate fibers have an average aspect ratio (fiber length / fiber diameter) of 5 to 200.
12. The friction material composition according to any one of claims 8 to 11, wherein the calcium sulfate fibers are fibers made of type II anhydrous gypsum.
13. A friction material composition described in any one of claims 8 to 12, wherein the content of the steel fibers is 1 mass % or less.
14. A friction material comprising the friction material composition according to any one of claims 8 to 13.
15. A vehicle equipped with the friction material according to claim 14.
Citation Information
Patent Citations
Manufacture of frictional material
JP1982043854A
Frictional material composition
JP1989238723A
Brake friction material
JP2001158904A
Friction material composition, and friction material and friction member using the same
JP2019048989A
Synchronizer ring
WO2004111479A1